2020
DOI: 10.1177/0022034520969115
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Intelligence in Dentistry

Abstract: Artificial intelligence (AI) is a technology that utilizes machines to mimic intelligent human behavior. To appreciate human-technology interaction in the clinical setting, augmented intelligence has been proposed as a cognitive extension of AI in health care, emphasizing its assistive and supplementary role to medical professionals. While truly autonomous medical robotic systems are still beyond reach, the virtual component of AI, known as software-type algorithms, is the main component used in dentistry. Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
160
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(162 citation statements)
references
References 57 publications
1
160
0
1
Order By: Relevance
“…AI models are bringing greater efficiency and accuracy, capitalizing on the interest, capabilities, and skills of those involved [ 48 ]. Effective and efficient interprofessional and clinician-patient interactions have evolved using these new ways, with AI students have new ways of learning through research and the data collected can be efficiently utilized for forensic and epidemiological uses [ 49 , 50 ]. Extensive research has been carried out on the application, benefits, and comparison of AI with human skills around the globe.…”
Section: Discussionmentioning
confidence: 99%
“…AI models are bringing greater efficiency and accuracy, capitalizing on the interest, capabilities, and skills of those involved [ 48 ]. Effective and efficient interprofessional and clinician-patient interactions have evolved using these new ways, with AI students have new ways of learning through research and the data collected can be efficiently utilized for forensic and epidemiological uses [ 49 , 50 ]. Extensive research has been carried out on the application, benefits, and comparison of AI with human skills around the globe.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of temporomandibular joint disorders (TMDs) can be detected based primarily on history and signs and symptoms, which are then to be followed by clinical examinations. Theoretically, the collective clinical data of TMDs examinations, if they can be translated into a well-structured and organized computer language, are able to differentiate between absolute TMDs diagnosis and other clinical conditions mimicking TMDs [ 65 ]. A study by Shoukri et al (2019) showed that the neural networks are able to program and classify the TMDs based on the combination of condylar radiographic imaging utilizing CBCT, biological markers such as saliva, and a variable range of clinical indicators including detailed facial and muscle pain and soreness history, range of mouth opening, and other signs such as headaches [ 66 ].…”
Section: Artificial Intelligence (Ai)mentioning
confidence: 99%
“…The dental practitioner and the auxiliary teams are responsible for data handling with potential risks of data privacy and security breaches. The AI/VR systems are not held accountable for this, though the application is performed either under supervision or not within the legal and jurisprudence context [ 65 , 67 ].…”
Section: Ethical Issues and Challenges In Ar/vr And Aimentioning
confidence: 99%
See 1 more Smart Citation
“…This will help improve decision-making in healthcare. The tasks for which this technology has been applied are of a preliminary nature ( 4 ). It has been used in medicine to aid diagnosis, interpretation of medical images, treatment planning, and prediction of treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%